Vibration Analysis Damage Detection in Structure - Sweta Verma; Pradeep Kumar Nirmal; Novel Kumar Sahu (International Journal of Scientific Research in Civil Engineering, 2022)
Steel, Power, and construction are indispensable industries for progressive growth of economic and social development. For maintenance, purposes are inspected on regular basis. The main point is to examine and is useful for the detection of surface damages cracks, concrete spalling in the structure, corrosion of steel members, and incomplete failure components, they can be particularly limited at detecting embedded and minor damage, For example fatigue cracks in the structure, corrosion of reinforcement, and delamination Structural health monitoring systems to replace conventional non-destructive inspection techniques which require considerable down-time, human effort and cost .Vibration based damage detection is the most promising techniques for implementation in Structural Health Monitoring (SHM) In the modern era, the concept of detection of damages based on dynamic measurement of structures is critical in focusing on the power of the modern city it is based, on changes in natural frequencies, flexibility and modal curvatures. The measurement of frequency for both before and after the damage to locate the damage and estimate its severity in shear buildings. These are the parameter to estimation are examined in detail reference to a masonry building affected by diffused damage. The changes induced by damage in the dynamic response are exploited to build a procedure for damage detection based on the variation of natural frequencies, both for continuous and discrete models.